Pengaruh Content Marketing, Viral Marketing dan Spiritual Marketing Terhadap Keputusan Pembelian dengan Minat Beli sebagai Variabel Intervening (Studi Pada Konsumen Rocket Chicken di Salatiga) - Sri Wahyuni; Saifudin (Al-Muraqabah: Journal of Management and Sharia Business, 2023)
The influence of viral marketing, content marketing, and spiritual marketing on purchasing decisions with purchase intention as an interesting intervening variable to study. The population of this research is Rocket Chicken Salatiga consumers. A total of 100 respondents were taken as samples using random sampling techniques. The author uses a quantitative method where the data sources are obtained from primary data and literature. The test statistical tools used were multiple linear regression analysis and path analysis which were processed with SPSS version 19 software. The research results proved that content marketing and viral marketing had no effect on purchasing decisions. However, spiritual marketing and buying interest have a positive and significant effect on purchasing decisions. Meanwhile, content marketing and spiritual marketing have a positive and significant effect on purchasing interest. Viral marketing has no effect on buying interest. Purchase interest is not able to mediate content marketing on purchasing decisions. Purchase interest is able to mediate viral marketing and spiritual marketing on purchasing decisions.